On Characteristics of \(ω\)-Anti-Q-Fuzzy Subgroups - Munusamy, Premkumar; Rathinakumar, V.; Suganya, R.; Kiruthika, K.; Venkatachalam, M.; Shanmugavel, P. (Mathematics and Computer Science: Research Updates Vol. 4, 2025)
On the aspect of fuzzy sets by L. A Zadeh, we first defined the definition of \(ω\)-anti-Q- fuzzy set and then explain the idea of \(ω\)-anti-Q-fuzzy subgroup. We also innovate the \(ω\)-Q-fuzzy normal subgroup and quotient group with respect to \(ω\)-anti-Q-fuzzy normal subgroup and constitute their several algebraic properties.